A new oxovanadium(IV)-cucurbit[6]uril complex: Properties and potential for confined heterogeneous catalytic oxidation reactions - de Lima, Silvania Marilene; Gomez, Jorge Antonio; Barros, Valeria P.; Vertuan, Greice de S.; Assis, Marilda das Dores; Graeff, Carlos Frederico de Oliveira [UNESP]; Demets, Gregoire Jean-Francois (Pergamon-Elsevier B.V. Ltd, 2010)
This work presents a new oxovanadium(IV)-cucurbit[6]uril complex, which combines the catalytic properties of the metal ion with the size-excluding properties of the macrocycle cavity. In this coordination compound, the VO(2-) ions are coordinated to the oxygen atoms located at the rim of the macrocycle in slightly distorted square-pyramidal configurations, which are in fact C(2v) symmetries. This combination results in a size-selective heterogeneous catalyst, which is able to oxidize linear alkanes like n-pentane at room temperature, but not styrene, cyclohexane or z-cyclooctene, which are too big to enter the cucurbit[6]uril cavity. The results presented here contribute to understanding the mechanism of alkane catalytic oxidation by oxovanadium(IV) complexes. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Cucurbit[6]uril; Oxovanadium(IV); Coordination compound; Size-selective catalysis